Phytobenthos in coastal waters of Blekinge and Kalmar counties 1990-2012 - Tobiasson, Stefan (Linnaeus University, 2021)
This database consist of data generated in recipient control programs in Kalmar and Blekinge Counties, Sweden.
The database consists of 22 tables. The data is mostly hard substrate vegetation and it's associated fauna, but also some vegetation cover data from sandy substrates.

Datamaterialet utgörs av insamlade kontrolldata efter beställning från Kalmar och Blekinge län. Data täcker främst vegetation på hårda substrat och dess tillhörande fauna, men även vegetation på sandiga substrat. Databasen består av 22 tabeller.
Phytobenthos i kustvatten i Blekinge och Kalmar län 1990-2012
Keywords: coastal management; phytobenthos biomass; Habitats and biotopes; Naturtyper och biotoper; Sea regions; Havsområden; Environment and conservation; Miljö och naturvård; Plants and animals; Växter och djur; Natural landscapes; Naturlandskap; Natural Sciences; Naturvetenskap; Environmental Sciences; Miljövetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Ecology; Ekologi; Biota; Biologi och ekologi; Oceans; Kust och hav